DETEKSI BAKTERI Salmonella DAN Shigella PADA MAKANAN BURGER DI SUNGAI RAYA DALAM PONTIANAK - Apriani, Lisa; Rahmawati, Rahmawati; Kurniatuhadi, Rikhsan (Universitas Tanjungpura, 2019)
Burger is one of the food in Indonesia that consists of bread, meat, vegetables, sauce, and mayonnaise. ThisÂ study aims to detect the bacterial presence from genus Salmonella and Shigella in burger food sold in Sungai Raya Dalam, Pontianak. Samples were collected from the location consist of cooked whole burger, precooked bread, postcooked bread, precooked burger meat, postcooked burger meat, lettuce, tomatoes, cucumbers, sauce, and mayonnaise ware bought from six traders. Based on the research, sixty samples tested in Salmonella Shigella Agar (SSA) media showed that 28,33% samples was contaminated with byÂ Salmonella and 3,33% samples was contaminated by Shigella, this showed that burger samples in Sungai Raya Dalam Pontianak could be contaminated by bacteria members of the genus Salmonella and ShigellaÂ and exceed the threshold that has been determined by SNI is negative / 25g